A novel ratiometric fluorescent probe from a hemicyanine derivative for detecting NAD(P)H in a cell microenvironment. Issue 14 (23rd March 2021) - Zhang, Jie; Liu, Zengchen; Tian, Fengshou; Chen, Yahong
Abstract : In this paper, a ratiometric fluorescent probe for NAD(P)H derived from coumarin and hemicyanine was synthesized. The ratiometric fluorescent probe provided an important theoretical basis for sensing NAD(P)H. Abstract : In this paper, a fluorescent compound derived from coumarin and hemicyanine was synthesized and characterized. Herein, we present the fluorescence properties of the probe. Fluorescence selectivity experiments revealed that it exhibited higher ratiometric fluorescence response activity toward NAD(P)H than other commonly coexisting compounds in the cell microenvironment, in accord with the fluorescence shift from red to blue. In addition, the fluorescence identification mechanism was deduced to be a redox reaction between the sensor and NAD(P)H according to the fluorescence behavior. The ratiometric fluorescent probe provided an important theoretical basis for sensing NAD(P)H in vitro and in vivo . We also used this phenomenon to build a sensitive detection platform of NAD(P)H-dependent enzyme activity based on the fluorescence method.